Ottoman Hunting Organization of Silistra Sanjak in The 16th Century - Mustafa ALKAN; Ferdi GÖKBUĞA (Gazi Akademik Bakış)
While hunting in traditional societies, was most commonly practised as a profession, for food, sports or entertainment, it was fully a part of Ottoman State organization as a military exercise or war game. From the first Ottoman rulers, there has been hunting institution in the palace. An organized hunting institution, regular hunting practices and the number of hunted animals had been perceived as the symbols of power of the ruler. Hunting organization was instrumental in identifying the situations of the country and people, inspecting government officials and listening to people’s problems. In this respect, the meaning of hunting ceremony gains great importance. Hunting bird-growing organization in Ottoman Empire palace had been institutionalized since early years. Its provincial administration was created for particular sanjaks. The structure of provincial hunting organization was organized in the form of taşra doğancıları (provincial falconers or hawkers), sayyad (hunters), yavrucu (fledgeling careres), yuvacı (nest carers), kayacı (carer of nest rocks), görenceci (bird observers), tuzakçı (bird catchers). There are records in Ottoman archives about this units concerning their organization, numbers, how they were spread and how the duties were passed from father to son. In this study, in the 16th century provincial Ottoman hunting organization and services in Silistra has been throughly examined, using archive documents.